2021
DOI: 10.3389/fspas.2021.701723
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Alternatives to the Hamiltonian Calculation of the Ashtekar-Olmedo-Singh Black Hole Solution

Abstract: In this article, we reexamine the derivation of the dynamical equations of the Ashtekar-Olmedo-Singh black hole model in order to determine whether it is possible to construct a Hamiltonian formalism where the parameters that regulate the introduction of quantum geometry effects are treated as true constants of motion. After arguing that these parameters should capture contributions from two distinct sectors of the phase space that had been considered independent in previous analyses in the literature, we proc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Despite all that, we expect that our results are robust regarding the breaking of isospectrality, which is the main result of this manuscript. Besides, although we have considered just a few effective geometries, we expect that isospectrality will also be broken in other black hole effective geometries [31,[42][43][44][45].…”
Section: Figmentioning
confidence: 99%
“…Despite all that, we expect that our results are robust regarding the breaking of isospectrality, which is the main result of this manuscript. Besides, although we have considered just a few effective geometries, we expect that isospectrality will also be broken in other black hole effective geometries [31,[42][43][44][45].…”
Section: Figmentioning
confidence: 99%
“…Nevertheless, the authors of Ref. [47] have indicated that this makes the relation between the proposed Hamiltonian and the dynamical equations unclear, given that an extra phase space dependent factor would enter the equations of motion should the non-trivial nature of the polymerization parameters be taken into account, leading to a more involved dynamics [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…In view of this situation, and focusing exclusively on the Hamiltonian derivation of the AOS solution, an alternative approach has been proposed in Ref. [48] to obtain the dynamical equations while considering the non-commutativity of the polymerization parameters with the canonical variables, bringing together a treatment of these parameters as true constants of motion and the undoubtedly interesting physical results of the original AOS model. In that paper, we introduced an alternative prescription for the selection of the polymerization parameters that extends the ideas of Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations